Influence of preparation method on mechanical characteristics of plaster - Igić Marko; Kostić Milena; Petković Dušan; Gligorijević Nikola; Dačić Stefan; Stošić Nenad (Medicinski fakultet i Klinika za stomatologiju, Niš, 2021)
Introduction: Plaster is widely used in dentistry for the production of master casts, as a binder in investment materials and as an auxiliary material in the laboratory stages of denture production. Due to its brittleness, there is a constant need to improve its mechanical properties. In this regard, in the research we started from the assumption that increasing the proportion of powder during the preparation of plaster improves its mechanical properties. The aim of this research wasto determine the significance of the change in the ratio of powder and liquid to the mechanical characteristics of plaster (compressive strength). Material and methods: Three types of plaster were used in the research: type 2, 3 and 4. For each type of plaster, three samples were made with different ratio of powder and amount of water (n = 9). After 24 hours, the samples were analyzed at the Faculty of Mechanical Engineering in Niš, on a universal testing machine. Results: Plaster type 2 showed the lowest values of compressive strength, and higher values of types 3 and 4, regardless of the ratio of plaster powder and water. As the powder content increased, the compressive strength of the samples increased. Conclusion: In order to improve the compressive strength, the proportion of powder in the liquid phase can be increased during the preparation of the material without visible changes in its structure.